The Effect of Work Discipline and Organizational Culture on Employee Morale with Work Motivation as an Intervening Variable at the Public Works and Spatial Planning Office of Boven Digoel Regency. - Murniati, Murniati; Ariadi, Wa; Meliala, Janita S. (East Asian Journal of Multidisciplinary Research, 2024)
This study discusses the effect of work discipline and organizational culture on employee morale with work motivation as an intervening variable at the Public Works and Spatial Planning Office of Boven Digoel Regency. This research uses quantitative methods with an associative approach. The results concluded that work motivation is not able to mediate the effect of work discipline on employee morale. The effect of organizational culture on employee morale at the Public Works and Spatial Planning Office of Boven Digoel Regency will be greater if done through work motivation. The direct effect of organizational culture on morale is smaller than the indirect effect of organizational culture on morale. It can be concluded that work motivation is able to mediate the effect of organizational culture on employee morale. Recommendations, the leadership of the Public Works and Spatial Planning Office of Boven Digoel Regency should improve work discipline by providing examples and disciplinary sanctions according to violations committed by subordinates, need to improve their organizational culture by increasing awareness in carrying out their responsibilities. To increase work enthusiasm, it can be done by providing motivation to each employee in order to create the desired goals.